Surgical outcomes of hepatocellular carcinoma with extrahepatic bile duct tumor thrombus: a multicenter study - Huang, Li-Ming; Zeng, Zhen-Xin; Wu, Jun-Yi; Li, Yi-Nan; Wang, Jin-Xiu; Fu, Yang-Kai; Wu, Jia-Yi; Wei, Shao-Ming; Lv, Jia-Hui; Chen, Wei-Zhao; Huang, Rong-Fa; Cheng, Shu-Qun; et al. (Frontiers in Oncology, 2023)
Background The long-term prognosis after surgery of patients with hepatocellular carcinoma (HCC) and extrahepatic bile duct tumor thrombus (Ex-BDTT) remains unknown. We aimed to identify the surgical outcomes of patients with HCC and Ex-BDTT. Methods A total of 138 patients with Ex-BDTT who underwent hepatectomy with preservation of the extrahepatic bile duct from five large hospitals in China between January 2009 and December 2017 were included. The Cox proportional hazards model was used to analyze overall survival (OS) and recurrence-free survival (RFS). Results With a median follow-up of 60 months (range, 1–127.8 months), the median OS and RFS of the patients were 28.6 and 8.9 months, respectively. The 1-, 3-, and 5-year OS rates of HCC patients with Ex-BDTT were 71.7%, 41.2%, and 33.5%, respectively, and the corresponding RFS rates were 43.5%, 21.7%, and 20.0%, respectively. Multivariate analysis identified that major hepatectomy, R0 resection, and major vascular invasion were independent prognostic factors for OS and RFS. In addition, preoperative serum total bilirubin ≥ 4.2 mg/dL was an independent prognostic factor for RFS. Conclusion Major hepatectomy with preservation of the extrahepatic bile duct can provide favorable long-term survival for HCC patients with Ex-BDTT.